Protecting Child Labor Rights: Maqasid Sharia Framework and Policy Recommendations - Yusefri, Yusefri; Faizin, Mu’adil; Jafar, Wahyu Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Child labor remains a significant issue in contemporary society despite existing legal frameworks aimed at protecting children's rights. This study presents an original approach by applying the principles of Maqasid Syariah to evaluate and strengthen child protection laws in Indonesia, specifically Law No. 35 of 2014 on Child Protection. The objectives of this research are to assess the effectiveness of the current legal framework in protecting child workers, identify its limitations, and explore how Maqasid Syariah principles can enhance these laws. The research employs a qualitative method, utilizing literature reviews and legal analysis to evaluate the existing legal framework and propose improvements based on Maqasid Syariah principles. Empirical findings reveal several limitations in the current legislation, including inconsistent implementation and enforcement, resource constraints, lack of coordination among stakeholders, insufficient awareness and education about children's rights, and the need to address the root causes of child labor, such as poverty and socio-economic inequalities. The practical implications of this study include recommendations to prioritize education, enforce strict labor protection regulations, enhance community training and awareness, encourage multi-stakeholder cooperation, and conduct regular monitoring and evaluation of child protection policies and programs. The study also highlights the importance of using the hierarchy of five protections (religion, life, intellect, lineage, and property) as indicators in evaluating child protection. By adopting a holistic approach grounded in Maqasid Syariah, this study proposes a new theoretical framework to integrate these principles with contemporary child protection laws. This offers a promising avenue for enhancing the effectiveness of child labor policies globally, ensuring that children grow up in a safe, healthy, and supportive environment, free from exploitation and hazardous working conditions.